Economic Digitalization And Network Society: Sociological Implications For Today's Network Society - Fita Sarah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research examines the broader sociological impacts of economic digitization on contemporary networked societies in Indonesia, amidst the accelerated social transformation due to the COVID-19 pandemic. Through literature review, it discusses how information and communication technology has become the primary enabler across various sectors of life, influencing consumer behavior and reshaping business structures. The research findings reveal that economic digitization not only redefines social interactions and business organization but also leads to the emergence of new phenomena in power dynamics, inequality, and social identity. The transition to technology-based business models also poses challenges in privacy, data security, and digital divide aspects. This article emphasizes the importance of inclusive policy responses to address sociological disparities and maximize digital economic opportunities. The research contributes significantly to contemporary sociology studies by highlighting the importance of equitable digital infrastructure development and digital literacy to ensure inclusive socio-economic sustainability in the networked era.